Serological Levels of Anticardiolipin, Antiphospholipid, TSH and HbA1c Levels in Randomly Selected Spontaneously Aborted Iraqi Females - Al-Mudhaffar, Zainab Salim Salih; khalfa, Hydar Muhsin (Journal of Science in Medicine and Life, 2025)
Abortion is defined as the termination of conception caused by the failure or removal of the embryo from the uterus before the conclusion of pregnancy. In another definition it is the pregnancy loss during fetal stage. Pregnancy loss is the most common adverse outcome for women expecting a baby. Many factors of abortion is remained unexplained. A successful pregnancy requires an accurate immunologic dialogue at the maternal-fetal immune interface in the endometrium. Autoimmune diseases (ADs), a category of complex diseases affecting nearly about 5% of the world population, can target a wide variety of tissues and organs. These diseases are characterized by the loss of self-tolerance and inappropriate activation of immune system, leading to the production of autoantibody and immune-mediated tissue destruction. Immunological and hormonal aberrancy may be considered a root cause of poor pregnancy outcomes. To evaluate the serological changes in relation to spontaneous abortion Methods: A total of 70 females undergoing spontaneous abortion in the first trimester were included in the study and compared to 33 normal healthy pregnant females with still births. Serological examination of Hba1c levels, anticaridiolipin IgM, IgG, antiphsolipid IgG, IgM and TSH levels were investigated. Subject Bmi and age were also correlated in this study. Conclusion: we conclude in this study factors include maternal age (generally associated with chromosomal anomalies leading to aneuploidy), maternal BMI, mental conditions like distress and anxiety are strongly associated with recurrent pregnancy loss.